Bridging the Gap: Collaborative Roles of Laboratory Technicians and Nurses in Enhancing Diagnostic Accuracy and Patient Care - Alotaibi, Yazeed Saad; Alqurashi, Lama Mohammed; Alshdoki, Ali Saleh; Alameer, Amal Abduljalil; Alkhabbaz, Ayat Alawi; Alsufyani, Rawan Mohammed; Almattar, Hussain Abdulkarim; Alhassan, Hashmiah Jaffar; Alabdi, Musallam Mohammed; Mobarki, Elham Ali; Alawami, Zallal Khadhr; Alsadiq, Zainab Ali; et al. (Journal of Posthumanism, 2024)
Collaboration in healthcare refers to the coordinated efforts of professionals from diverse disciplines working together to achieve shared goals in patient care. This framework recognizes that optimal outcomes are achieved when specialized expertise from various fields is integrated into a unified care process. Nurses, laboratory technicians, physicians, and pharmacists each provide distinct yet complementary competencies that support accurate diagnosis, effective treatment, and successful recovery.